2012
DOI: 10.1007/978-3-642-27494-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Scanning Probe Microscopy: An Overview

Abstract: In this chapter, which serves as an introduction to the entire book, an overview is given of techniques resulting from the synergy between ultrasonic methods and scanning probe microscopy (SPM). Although other acoustic SPMs have been developed, those reviewed in this book are either the earliest proposed techniques, which are most widespread, extensively used, and continuously improved, or have been recently developed, but have been proved to be extremely promising. The techniques are briefly introduced, empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 124 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the lattice spontaneous polarization is rotated at the domain wall, resulting in a smaller average polarization and stiffening at the domain wall compared to the domains. [ 24,25 ] However, those studies only reported the mechanical softening of 180 o domain walls compared to their surrounding domains. Thus, more comprehensive studies that focus on the behavior of 90 o domain walls compared to their surrounding domains are still needed as well as the use of different AFM modes to access the intrinsic mechanical properties to investigate the big picture of the mechanical properties of the ferroelectric PTO single crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lattice spontaneous polarization is rotated at the domain wall, resulting in a smaller average polarization and stiffening at the domain wall compared to the domains. [ 24,25 ] However, those studies only reported the mechanical softening of 180 o domain walls compared to their surrounding domains. Thus, more comprehensive studies that focus on the behavior of 90 o domain walls compared to their surrounding domains are still needed as well as the use of different AFM modes to access the intrinsic mechanical properties to investigate the big picture of the mechanical properties of the ferroelectric PTO single crystal.…”
Section: Introductionmentioning
confidence: 99%